The Boundary-Scan Handbook - Parker, Kenneth P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Aimed at electronics industry professionals, this 4th edition of the Boundary Scan Handbook describes recent changes to the IEEE1149.1 Standard Test Access Port and Boundary-Scan Architecture. This updated edition features new chapters on the possible effects of the changes on the work of the practicing test engineers and the new 1149.8.1 standard. Anyone needing to understand the basics of boundary scan and its practical industrial implementation will need this book. Provides an overview of the recent changes to the 1149.1 standard and the effect of the changes on the work of test engineers;   Explains the new IEEE 1149.8.1 subsidiary standard and applications;   Describes the latest updates on the supplementary IEEE testing standards. In particular, addresses: IEEE Std 1149.1                      Digital Boundary-Scan IEEE Std 1149.4                      Analog Boundary-Scan IEEE Std 1149.6                      Advanced I/O Testing IEEE Std 1149.8.1                    Passive Component Testing IEEE Std 1149.1-2013                 The 2013 Revision of 1149.1 IEEE Std 1532                        In-System Configuration IEEE Std 1149.6-2015                 The 2015 Revision of 1149.6.
Boundary-Scan Basics And Vocabulary.-  Boundary-Scan Description Language (BSDL) -- Boundary-Scan Testing -- Advanced Boundary-Scan Topics -- Design for Boundary-Scan Test -- Analog Measurement Basics -- IEEE 1149.4 Analog Boundary-Scan.-  IEEE 1149.6 Testing Advanced I/O.-  IEEE 1532:In-System Configuration -- IEEE 1149.8.1: Passive Components -- IEEE 1149.1:The 2013 Revision.-  IEEE 1149.6: The 2015 Revision.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Semiconductors; Electronic Circuits and Systems; Processor Architectures; Semiconductors